Reconstructing a millennial‐scale record of flooding in a single valley setting: the 2011 flood‐affected Lockyer Valley, south‐east Queensland, Australia. (November 2016) - Croke, Jacky; Thompson, Christopher; Denham, Robert; Haines, Heather; Sharma, Ashneel; Pietsch, Timothy
ABSTRACT: This paper reconstructs past flooding from a range of settings in Lockyer Creek, a key tributary of the mid‐Brisbane River, which experienced extreme flood events in AD 2011 and AD 2013. Optically stimulated luminescence samples ( n  = 110) were collected from alluvial material preserved in within‐channel benches and floodplains. Age distributions from material in the bedrock reaches confirm an event ∼ 300 years ago which stripped the valley alluvium to bedrock. In the unconfined reaches floodplain deposits indicate lateral stability over the past 6000 years. Marked differences in the inundation patterns of the AD 2011 event highlighted changes in downstream channel geometry. The age distribution of alluvium in reaches not inundated during AD 2011 was older, ∼12 000 years, with no preserved evidence of deposition during the past 1000 years. A relatively continuous record of floodplain deposition in reaches which were inundated in AD 2011 identifies a major peak in flood activity also around 300 years ago (∼AD 1730) with five additional peaks occurring at approximately AD 1962, AD 1897, AD 1300, AD 550 and 5400 BC. The main climatic driver of changes in flooding over this timescale is oscillations in El Niño Southern Oscillation and although proxy records are scarce for this region, some correlations with high‐resolution records of rainfall variability are apparent.